DAILY – A personalized circadian Zeitgeber therapy as an adjunctive treatment for alcohol use disorder patients: results of a pilot trial - Springer, Naomi; Echtler, Lisa; Volkmann, Paul; Hühne-Landgraf, Anisja; Hochenbleicher, Jasmin; Hoch, Eva; Koller, Gabi; Landgraf, Dominic (Frontiers in Psychiatry, 2025)
BackgroundDisturbances of circadian rhythms and everyday structures are hallmarks of alcohol use disorder (AUD). Recurring activities such as sleep, activity, and meals represent time cues, so called Zeitgebers, that synchronize the circadian system. With our newly developed therapy approach for AUD patients, we aim to reduce relapses and alcohol consumption in AUD patients undergoing a withdrawal program by strengthening their circadian rhythms.Methods/DesignWe aim to achieve the improvement of circadian rhythms with personalized structure plans for daily Zeitgeber activities, which are used in parallel with the standard therapy at our clinic. The DAILY pilot study is a six-week monocentric trial with a controlled, randomized, single-blinded, parallel-group design. 41 AUD patients participated in the pilot study and were randomly assigned to an intervention group (IG) or a control group (CG).ResultsThe variability of daily activities was significantly lower in the IG group than in the CG group. Of the IG participants, two had relapsed during the study (<12%), whereas ten relapsed in the CG group (>60%). The relapsing IG participants recorded a total of three alcohol consumption days, while the CG participants recorded 52 consumption days. Abstinent participants showed significantly less variability in the times of their daily activities than relapsed participants. In addition, our analyses indicate that craving for alcohol is related to variability in the time of getting up and that craving and temporal variability increase before relapses. Moreover, the general well-being of the IG participants improved more than that of the CG participants.DiscussionThe data from this pilot study show that following a personalized daily structure plan helps AUD patients to remain abstinent during withdrawal therapy. The analyses indicate that temporal variability of daily activities and the risk of relapse are correlated. On the one hand, adherence to the daily structure may prevent relapse, on the other hand, an increase in variability may be a helpful predictor of approaching relapse. In our view, these data justify a continuation of the DAILY study with the addition of further measurements such as the determination of endogenous circadian rhythms.Clinical trial registrationhttps://drks.de, identifier DRKS00019093.